Interference Cancellation Using Space-Time Processing and Precoding Design - Li, Feng (Signals and Communication Technology,, 2013)
Interference Cancellation Using Space-Time Processing and Precoding Design introduces original design methods to achieve interference cancellation, low-complexity decoding and full diversity for a series of multi-user systems. In multi-user environments, co-channel interference will diminish the performance of wireless communications systems. In this book, we investigate how to design robust space-time codes and pre-coders to suppress the co-channel interference when multiple antennas are available.   This book offers a valuable reference work for graduate students, academic researchers and engineers who are interested in interference cancellation in wireless communications. Rigorous performance analysis and various simulation illustrations are included for each design method.   Dr. Feng Li is a scientific researcher at Cornell University.